Defining and managing incidental findings in genetic and genomic practice. Issue 11 (16th September 2014) - Shkedi-Rafid, Shiri; Dheensa, Sandi; Crawford, Gillian; Fenwick, Angela; Lucassen, Anneke
Abstract : The rapidly declining costs and increasing speeds of whole-genome analysis mean that genetic testing is undergoing a shift from targeted approaches to broader ones that look at the entire genome. As whole-genome technologies gain widespread use, questions about the management of so-called incidental findings—those unrelated to the question being asked—need urgent consideration. In this review, we bring together current understanding and arguments about (1) appropriate terminology, (2) the determination of clinical utility and when to disclose incidental findings, (3) the differences in management and disclosure in clinical, research and commercial contexts and (4) ethical and practical issues about familial implications and recontacting those tested. We recommend that greater international consensus is developed around the disclosure and management of incidental findings, with particular attention to when, and how, less clear-cut results should be communicated. We suggest that there is no single term that captures all the issues around these kinds of findings and that different terms may, therefore, need to be used in different settings. We also encourage the use of clear consent processes, but suggest that the absence of consent should not always preclude disclosure. Finally, we recommend further research to identify ways to implement the use of a genome output as a resource, accessible over time, to facilitate appropriate disclosure and recontact when the significance of a previously unclear incidental finding is clarified.